Distribution and palynological characteristies of Encalyptus honey from Galicia (NW Spain) - Aira Rodríguez, María Jesús; Jato Rodríguez, Victoria; Seijo Coello, María Carmen (Botanica Complutensis, 1998)
SEIJO, MC., AIRA, M.J. & JATO, MV- 1998. Distribution and palynological caracteristies of Eucaivptus honey from Galicia (NW Spain). BoL Complutensis 22: 133-143. We have realized the melissopalynologycal study of 60 honey samples from Galicia, with percentages higher than 70% of Eucalyptus pollen, so these samples were considered monofloral honeys. Ihe 10% of the samples had values of Eucalyptus pollen higher than 89%, 34% had values between 80% and 89% and the rest (56%) had values between 70% and 79%. The mean of pollen types in the pollen spectrum of honeys was 25 and its honeydew content was zero. Related to its pollen content tese honeys were poor in pollen with an average of 4.753 pollen grains per gr-am of honey. Generally, Eucalvptus honeys from Galicia show later crystal¡ization and amber colour.
Keywords: Pollen; honey; Eucaivpíus; Galicia